2021
DOI: 10.26656/fr.2017.5(1).372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foaming agent concentration and drying temperature on biochemical properties of foam mat dried tomato powder

Abstract: The purpose of the study was to optimize the effective drying conditions and different foaming agent concentrations on the biochemical properties of foam mat dried tomato powder. Foaming was achieved by using egg albumin as foaming agent and sodium salt of Carboxymethyl Cellulose (CMC) as foam stabilizer with different concentrations. Drying was achieved by using different drying temperatures. The changes in different physicochemical properties of foam mat dried powder viz. total soluble solid (TSS), pH, ascor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The high temperature increased the evaporation rate, and the higher evaporation rate can damage the products’ cell, which was responsible for increasing the polyphenol enzyme activity ( Whitesides et al, 2001 ). Hossain et al, 2020a , Hossain et al, 2021b ) observed the decrease of phenolic content with the increase of temperature in moringa leaves and legumes, respectively. Another probable reason for the decrease of TPC could be the effect of pretreatment.…”
Section: Discussionmentioning
confidence: 96%
“…The high temperature increased the evaporation rate, and the higher evaporation rate can damage the products’ cell, which was responsible for increasing the polyphenol enzyme activity ( Whitesides et al, 2001 ). Hossain et al, 2020a , Hossain et al, 2021b ) observed the decrease of phenolic content with the increase of temperature in moringa leaves and legumes, respectively. Another probable reason for the decrease of TPC could be the effect of pretreatment.…”
Section: Discussionmentioning
confidence: 96%
“…As plum fruit has 9–10% sugar content, foam mat drying would be a viable choice for the dehydration process. In this process, liquid or semiliquid food is whipped with a foaming agent to produce a stable foam by integrating a sufficient proportion of air, resulting in a porous structure with a high rate of heat and mass transfer when dehydrated [ 16 ]. The overall process time is greatly reduced in a lower temperature, and thus, a product with better nutritional quality can be obtained [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Pinelo et al (2005), extraction temperature more than 50 °C may alter the phenolic compounds, stability and affects integrity of plants' membrane [32]. This might be a fundamental reason behind decreasing the activity [33][34][35]. Hossain et al (2020a, b) also reported similar results for antioxidant extraction from moringa leaves and jackfruit pulp and seed [7,12].…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%